PENDEKATAN JOYFUL LEARNING DALAM PENGENALAN KEMAMPUAN CALISTUNG PADA SISWA PRASEKOLAH - Nurkamila, Hanifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT There are many methods and techniques that can be used to implement a joyful learning approach in effective learning of reading, writing, and arithmetic (calistung). The concept of joyful learning is very suitable for preschool students because the enjoyable learning concept can engage and capture students' attention, as some of the methods used involve the concept of play, which is essentially a learning concept suitable for early childhood, that is, learning through play. The purpose of this research is to understand the Joyful Learning approach in introducing reading, writing, and arithmetic skills to preschool students. The method used is Systematic Literature review by tracing previous research related to the research topic. The results indicate that several methods/strategies that can be used in the joyful learning approach include the methods or techniques and media used, which are able to support children to be actively involved in the learning process, attract children's attention, and make children more focused during the reading, writing, and arithmetic learning process. In addition, the lack of media and teacher competence becomes a challenge in applying the joyful learning approach in reading, writing, and arithmetic learning.